Effects of inadequate coverage on healthcare utilization: A regression discontinuity analysis. Issue 20 (21st May 2021) - Dugan, Jerome A.; Booshehri, Layla G.
Abstract : Abstract: To examine the impact of inadequate health insurance coverage on physician utilization among older adults using a novel quasi-experimental design in the time period following the elimination of cost sharing for most preventative services under the US Affordable Care Act of 2010. The Medical Expenditure Panel Survey full year consolidated data files for the period 2010 to 2017 were used to construct a pooled cross-sectional dataset of adults aged 60 to 70. Regression discontinuity design was used to estimate the impact of transitioning between non-Medicare and Medicare plans on use of routine office-based physician visits and emergency room visits. For the overall population, gaining access to Medicare at age 65 is associated with a higher propensity to make routine office-based visits (2.94 percentage points [pp]; P < .01) and lower out-of-pocket costs (−23.86 pp; P < .01) Similarly, disenrollment from non-Medicare insurance plans at age 66 was associated with more routine office-based visits (3.01 pp; P < .01) and less out-of-pocket costs (−8.09 pp; P < .10). However, some minority groups reported no changes in visits and out-of-pocket costs or reported an increased propensity to make emergency department visits. Enrollment into Medicare from non-Medicare insurance plans was associated with increased use of routine office-based services and lower out-of-pocket costs. However, some subgroups reported no changes in routine visits or costs or an increased propensity to make emergency department visits. These findings suggest other nonfinancial, structural barriers may exist that limit patient's ability to access routine services.